An evidence-based assessment of variation in equine hoof conformations to farriery techniques in Federal Territory and Selangor stables, Malaysia - Awang Kamaludin, Dayang Norhaizum; Fateh Mohamed, Bashir Ahmad (2012)
Equine hoof plays an important role in the performance of horses. There is minimal research done on hoof conformation in Malaysia. This study was carried out in 5 established stables in Federal Territory and Selangor, to determine how different farriery interventions could affect the conformation of the hoof, and to provide basic data on hoof measurements. A total of 54 actively shod and sound working horses were used to assess all limbs for hoof angle (HA), quarter width (QW), sole length (SL), frog length (FL) and width (FW), heel width (HW) and height (HH), toe length (TL), hoof pastern axis (HPA), sole concavity, and wear and tear of shoes. There were no significant differences in hoof assessments in horses managed by different farriers. However, this study showed that the common faults in farriery including low HA, long toes, low HH, and narrow frog. These farriery faults can eventually cause internal foot injuries and lameness in horses. Hence, proper farriery techniques should be implemented to produce sound and better performance horses.